Domiciliary non‐invasive ventilation post lung transplantation. Issue 1 (24th August 2017) - Kotecha, Sakhee; Buchan, Catherine; Parker, Kerry; Toghill, Jo; Paul, Eldho; Miller, Belinda; Naughton, Matthew; Snell, Gregory; Dabscheck, Eli
ABSTRACT: Background and objective: The benefits of domiciliary non‐invasive ventilation (NIV) post lung transplantation (LTx) have not previously been described. This was a single‐centre retrospective audit of patients requiring domiciliary NIV post‐LTx. Our aim was to describe indications for NIV and outcomes in chronic lung allograft dysfunction (CLAD) and diaphragmatic palsy. Methods: All patients requiring domiciliary NIV post‐LTx between 2010 and June 2016 were assessed. NIV indications, respiratory function and patient outcomes were collected. Results: Out of 488 LTx recipients, 20 patients were identified as requiring NIV over the 6.5‐year study period. The most common indications for NIV were CLAD and diaphragmatic palsy. Hypercapnia improved significantly with NIV. Patient outcomes were poor with nine (45%) patients dying, four (20%) undergoing redo‐LTx, four (20%) continuing domiciliary NIV and only three (15%) patients weaned off NIV. Conclusion: This is the first case series to describe the use of domiciliary NIV post‐LTx. Patients commenced on NIV post‐LTx had severely impaired lung function and severe hypercapnia. Patients with diaphragmatic palsy often recovered. The mortality rate was high in chronic allograft dysfunction. Abstract : Domiciliary non‐invasive ventilation (NIV) post lung transplantation (LTx) is seldom required. LTx recipients with ventilatory failure secondary to chronic lung allograft dysfunction may benefit from NIV as a bridge to redo‐LTx or as a palliative measure. LTx recipients with diaphragmatic palsy may be weaned off NIV as they recover.